Comparing US public university and US private sector project costs. Issue 2 (10th December 2018) - Strong, Kelly; Glick, Scott; Syhail, Gazala
Abstract : Purpose: This study aims to focus on the factors influencing project cost at US public universities and compares them to similar projects in the US private sector. It also presents an analysis of the potential reasons for the difference or similarities in the two sectors. Design/methodology/approach: This study utilized an exploratory, comparative case study methodology performed on a small sample of public university projects and two sources of private sector cost data. Findings: The results infer that most of the US public projects have comparable costs to that of their US private sector counterparts. The cost data from the university projects were further examined to explore if there were any possible relationships between the types of delivery methods used, sustainability certifications achieved and two project performance indexes – cost and duration. Research limitations/implications: A more thorough analysis with a larger dataset is required to make generalizable conclusions. However, the process used in this study does provide a good overview of how facility managers could organize their own cost comparison study to evaluate their project expenditures. Practical implications: This research provides a starting point for future research into the topic of US public sector project costs when compared to US private sector counterparts and the impact of delivery system and sustainability on cost of US public sector projects. Originality/value: Research on this topic is scant; as such, this paper provides a starting point for future research and offers insights into the potential impacts of project delivery method and choice of following a sustainability certification option.